Trains, literature, and culture reading/writing the rails - Spalcing, Steven D.; Fraser, Benjamin (Lanham, Maryland. Lexington Books, 2012)
"Trains, literature and culture is the first work to thoroughly explore the railroad's connections with a full range of cultural discourses--including literature, visual art, music, graffiti, and television but also advertising, architecture, cell phones, and more ..."--Provided by publisher.
Railroad blues : crossing the tracks of gender, class, and race inequities in the blues and Ann Petry's The street / Claudia May -- Nineteenth-century German women writers on the railroad / Beth Muellner -- Technology transfer, the railway and independence in Ousmane Sembène's Les bouts de bois de Dieu / Roxanna Curto -- Futurist trains : aesthetics and subjectivity in the Italian avant-garde / Alessio Lerro -- Sublime hieroglyphics : the Pacific Coast views 1867-1872 of Carleton Watkins / Scott Palmer -- Modernity, anxiety, and the development of a popular railway landscape aesthetic, 1809-1879 / Matt Thompson -- Mapping memory through the railway network : reconsidering Freud's metaphors from the Project for a scientific psychology to Beyond the pleasure principle / Claudie Massicotte -- Killer trains and thrilling travels : the spectacle of mobility in Zola and Proust / Steven D. Spalding -- Class and counterfeiting during the Porfiriato : Gutièrrez Nájera's "The streetcar novel" / José Eduardo González -- Train, trestle, ticker : railroad and region in Frank Norris's The octopus and María Amparo Ruiz de Burton's The squatter and The Don / Michael Velez.
Keywords: Railroads in literature; Literature -- History and criticism. -- 19th century; Literature -- History and criticism. -- 20th century